ANALYSIS OF STUDENTâ€™S BOOK ON FOURTH GRADE BASED ON CURRICULUM 2013 THEMES "MY HEROES" SUBTEMA "THE STRUGGLE OF THE HEROES" - Bernadine Ajeng Indriasari (JISAE: Journal of Indonesian Student Assessment and Evaluation, 2017)
The purpose of this research is to know stundentâ€™s book of four grade student based on Curricullum 2013 on theme â€œPahlawankuâ€ subtheme â€œPerjuangan Para Pahlawanâ€ on lesson 3with kompetensi dasar, purpose, indicator, learning activity, materials, tool and learning resources. Research method is descriptive method by analyze document is student book of four grade student based on Curricullum 2013 on theme â€œPahlawankuâ€ and teacher book of four grade student based on Curricullum 2013. The analize revolves on the rule of Menteri Pendidikan dan Kebudayaan Nasional, an article discussing about the implementation of Curricullum 2013 and article from Badan Nasional Standar Pendidikan (BSNP) website. The result of this research are found that some kompetensi dasar do not appear in indicators and materials that are less in line with the mapping of kompetensi dasar. From the analysis it is conclude that the studentâ€™s book of four grade student based on Curricullum 2013 on theme â€œPahlawankuâ€ subtheme â€œPerjuangan Para Pahlawanâ€needs much improved with the discrepancies inlesson 3.